DESIGN OF A WEB-BASED FISH SALES INFORMATION SYSTEM TO IMPROVE MARKETING EFFICIENCY USING THE WATERFALL MODEL - Dewi Syarifatunnisak; Putri Amelia (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The development of aquaculture activities requires effective sales and marketing management to support business sustainability. This study aims to design and build a web-based fish sales information system to improve marketing efficiency and operational performance at the Cerme Rice Pond, Gresik Regency. Problems encountered include manual recording of sales and inventory, inconsistencies in stock data, and delays in report preparation, which impact service quality and managerial decision-making. The method used in this study is the Software Development Life Cycle (SDLC) with the Waterfall model, which includes the stages of needs analysis, system design, implementation, and testing. The system was developed web-based to integrate the management of fish data, inventory, sales transactions, operational activities, and reports in one centralized database. System testing was conducted using the black-box testing method to ensure functional suitability, and User Acceptance Testing (UAT) using a Likert scale to measure the level of user acceptance. The results of the study indicate that the developed system is able to improve data recording accuracy, accelerate real-time information access, and support the preparation of structured sales reports. The UAT results obtained a score of 85.6%, categorized as very good , indicating that the system is acceptable to users and meets the operational needs of the ponds. The novelty of this research lies in the implementation of an integrated web-based fish sales information system specifically designed to support marketing efficiency in village-scale aquaculture businesses.